Leprosy Patients in Public Perception: A Qualitative Study of Patient Confidence in The Community - sodik, muhammad ali (Journal of Global Research in Public Health, 2016)
Leprosy is a disease caused by Mycobacterium leprae. Data show that in East Java is still widely spread in the district leprosy including Psychology. The purpose of research is to explore the public acceptance of leprosy patients in Work Area Puskesmas Kampak Trenggalek Regency. This study uses qualitative data approach taking the sample using purposive sampling technique. This data was taken with in-depth interviews and observations in communities around the area of lepers at Puskesmas Kampak Trenggalek Regency covering lepers family, neighbors, co-workers and community leaders as well as lepers itself The results showed that patients with leprosy many changes towards a negative self-concept. While some informants did not receive and accept leprosy patients in the community.